Maintenance of sinus rhythm after electrical cardioversion to identify patients with persistent atrial fibrillation who respond favorably to pulmonary vein isolation: the pre-pacific study - Limite, Luca Rosario; Laborie, Guillaume; Ramirez, F. Daniel; Albenque, Jean-Paul; Combes, Stephane; Lagrange, Philippe; Khoueiry, Ziad; Bortone, Agustín (Frontiers in Cardiovascular Medicine, 2024)
Background: Pulmonary vein isolation (PVI) is successful in approximately 50% of patients with persistent atrial fibrillation (PsAF) at one year. Identifying pre-procedurally the patients who respond favorably to a PVI alone strategy could improve their management. The present study aims to assess the predictive value of clinical response to pre-ablation electrical cardioversion (ECV) to identify the responders to PVI.Methods: Consecutive patients undergoing catheter ablation for PsAF were retrospectively classified, as "ECV successful" vs "ECV failure", according to the rhythm of presentation after an ECV performed ³4 weeks. Clinical and procedural data were analyzed in both groups according to the ablation strategy applied (PVI vs PVI + substrate modification).Results: In total, 58 patients (39.4%) had successful ECVs and 89 (60.6%) had failed ECV. Preprocedural characteristics were similar in both groups. Compared to the ECV failure group, patients with successful ECV presented less frequently (34% vs. 60%; P=0.004) and less extended (21.3±22.2% vs. 38.9±27.4% of LA surface, P=0.008) low-voltage areas. Over 55 ± 19 weeks of follow-up, AF-free survival was similar in both groups (72.7% vs 67.8%, p=0.39). PVI alone resulted in 83% AF-free survival among patients in the ECV successful group at 13 months.In approximately 40% of patients with PsAF, sinus rhythm can be restored by ECV and maintained for at least 1 month prior to catheter ablation. This clinical response is associated with less abnormal substrate as identified by left atrial voltage mapping and a procedural success rate of >80% with PVI alone.